Fault isolation in multicast trees. - Reddy, Anoop
Fault isolation has received little attention in the Internet research literature. We take a step towards addressing this deficiency, exploring robust and scalable techniques by which multicast receivers can (in some cases, approximately) locate the on-tree router responsible for a route change, or the link responsible for significant packet loss. A common property of our techniques is that receivers with overlapped paths coordinate to share the responsibility of monitoring paths to the source. Our techniques assume no additional path monitoring capability other than that provided by multicast traceroute (mtrace).
Keywords: Computer systems organization; Computer communication networks; Local and Wide-Area Networks; Internet (e.g., TCP/IP).; Network protocols; TCP IP; Mathematics of computing; Discrete mathematics; Graph theory; Trees; Design; Measurement; Performance; Reliability; Standardization; Theory